2020
DOI: 10.1111/jcpe.13358
|View full text |Cite
|
Sign up to set email alerts
|

Salivary proteotypes of gingivitis tolerance and resilience

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…It is known from the literature that MMP-8 and MMP-9 have similar specificity to degrade matrix, and they have the same inhibitors (e.g. TIMP-1) 3 , 20 22 . When comparing the gingivitis vs health groups, the values of the above biomarker relations were of the same order as the values of the single biomarkers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known from the literature that MMP-8 and MMP-9 have similar specificity to degrade matrix, and they have the same inhibitors (e.g. TIMP-1) 3 , 20 22 . When comparing the gingivitis vs health groups, the values of the above biomarker relations were of the same order as the values of the single biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…To validate a subset of existing candidate protein markers that are most relevant for periodontal disease, we performed ELISA-based analysis in a cross-sectional cohort, using saliva as a diagnostic biological fluid. During the past years, emerging protein detection technologies have revealed a large number of candidate periodontitis biomarkers 3 , 20 . Unfortunately, there exists a big gap between biomarker discovery and validation due to several factors 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude and consistency of immune-inflammatory response are controlled at a number of regulatory, genetic and epigenetic levels that likely influence the individual variability in the severity and rate of progression of the disease. Consistently, experimental gingivitis studies have revealed that the intensity of the gingival inflammation in periodontitis-susceptible patients is strictly related to the individual inflammatory host response rather than being entirely due to differences in the amount and composition of the bacterial biofilm [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 90%
“…However, the composition of the oral or tooth-specific microbiome may not be exclusively associated with the maintenance of oral health or disease [ 16 ]. It has been shown that patients who abstain from oral hygiene procedures subsequently develop different responses to their accumulated plaque [ 13 , 17 , 18 ]. These different clinical responses enabled a classification into “periodontal-resistant” and “periodontal-insufficient” or ”high responder” and “low responder”, respectively [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that patients who abstain from oral hygiene procedures subsequently develop different responses to their accumulated plaque [ 13 , 17 , 18 ]. These different clinical responses enabled a classification into “periodontal-resistant” and “periodontal-insufficient” or ”high responder” and “low responder”, respectively [ 18 ]. Hence, the host’s response to pathogenic stimuli also accounts for the maintenance of oral health or development of disease.…”
Section: Introductionmentioning
confidence: 99%